Estimating Parameters via L-Linear Method for Second-Order Regression of Polynomial Model - Younis Mohammad, Mahdi; Dheyab Ahmed, Ahmed (Journal of Economics and Administrative Sciences, 2022)
In this paper, estimation of the parameters of the second-order polynomial regression model was obtained when the error is distributed it is distribution long-tailed symmetric because of the presence of outliers and using Maximum Likelihood, and L-Method. simulation is illustrated, and Mean Squared Error (MSE) is used as an evaluation criterion. This research includes six sample sizes (50,60,80,90,100,120) and includes the application of the methods of the medical data representing diabetes. Paper type Research paper.